Muscular dystrophy candidate gene FRG1 is critical for muscle development - Hanel, Meredith L. (2009)
The leading candidate gene responsible for facioscapulohumeral muscular dystrophy (FSHD) is FRG1 (FSHD region gene 1). However, the correlation of altered FRG1 expression levels with disease pathology has remained controversial and the precise function of FRG1 is unknown. Here we carried out a detailed analysis of the normal expression patterns and effects of FRG1 misexpression during vertebrate embryonic development using Xenopus laevis. We show that frg1 is expressed in and essential for the development of the tadpole musculature. FRG1 morpholino injection disrupted myotome organization and led to inhibited myotome growth while elevated FRG1 led to abnormal epaxial and hypaxial muscle formation. Thus, maintenance of normal FRG1 levels is critical for proper muscle development, supportive of FSHD disease models whereby misregulation of FRG1 plays a causal role underlying the pathology exhibited in FSHD patients.